Efforts to Improve Students' Creative Thinking Skills by Implementing the Discovery Learning Model in Mathematics Learning at MIN 20 Pidie Jaya - Rauzatul Jannah; Intan Aisara (DEEP LEARNING: Journal of Educational Research, 2025)
This classroom action research aimed to improve students’ creative thinking skills in mathematics learning through the implementation of the Discovery Learning model at MIN 20 Pidie Jaya. The study was conducted due to the low level of students’ creative thinking abilities, particularly in generating diverse solution strategies, developing original ideas, and elaborating mathematical reasoning during classroom activities. The participants consisted of 28 fifth-grade students. The research was carried out in two cycles, each comprising four stages: planning, action, observation, and reflection. Data were collected through creative thinking skill tests, observation sheets of teacher and student activities, and documentation. The indicators of creative thinking assessed in this study included fluency, flexibility, originality, and elaboration. The findings revealed a significant improvement in students’ creative thinking skills after the implementation of Discovery Learning. The average score of students’ creative thinking skills increased from 62.14 in the pre-cycle to 72.86 in Cycle I and further improved to 84.29 in Cycle II. In addition, the percentage of students achieving mastery learning increased from 42.86% in the pre-cycle to 67.86% in Cycle I and reached 89.29% in Cycle II. Observation results also showed improvement in student engagement and participation, where the average student activity score increased from 70.00% in Cycle I to 88.00% in Cycle II. These results indicate that the Discovery Learning model effectively enhances students’ creative thinking skills in mathematics learning by encouraging active exploration, problem-solving, and concept discovery. Therefore, Discovery Learning is recommended as an alternative instructional model to foster creativity and higher-order thinking skills in elementary mathematics classrooms.